2016
DOI: 10.1017/ice.2015.346
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas aeruginosa Colonization in the Intensive Care Unit: Prevalence, Risk Factors, and Clinical Outcomes

Abstract: OBJECTIVE Determine the prevalence of Pseudomonas aeruginosa colonization on ICU admission, risk factors for P. aeruginosa colonization, and the incidence of subsequent clinical culture with P. aeruginosa among those colonized and not colonized. DESIGN A cohort study of patients admitted to the medical or surgical intensive care units between January 1, 2013, and December 31, 2013. SETTING A tertiary care hospital in Maryland. RESULTS 213 patients of 1840 patients (11.6%) were colonized with P. aeruginos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 20 publications
1
36
1
2
Order By: Relevance
“…Studies that investigate PA colonization as a risk factor for subsequent PA infection are very scarce, and they do not perform multivariate time-to-event analysis in combination with competing risk analyses [3, 4, 79]. …”
Section: Discussionmentioning
confidence: 99%
“…Studies that investigate PA colonization as a risk factor for subsequent PA infection are very scarce, and they do not perform multivariate time-to-event analysis in combination with competing risk analyses [3, 4, 79]. …”
Section: Discussionmentioning
confidence: 99%
“…21 A study by Harris et al to investigate the prevalence of P. aeruginosa colonisation on ICU admission, revealed that of the 1 840 patients, 213 (11.6%) were colonised with P. aeruginosa on ICU admission. 22 In another study on frequency of multi-drug resistant (MDR) P. aeruginosa in intensive care unit (ICU)-acquired pneumonia (ICUAP), P. aeruginosa was the most frequent aetiology of ICUAP (64, 29%). 23 These are in line with our studies where 82% of the isolates were recovered from the ICUs.…”
Section: Discussionmentioning
confidence: 99%
“…In this study and in prior studies, the positive and negative predictive values of the fields in the electronic medical record/central data repository were greater than 99%. 10-13 …”
Section: Methodsmentioning
confidence: 99%